PEGylated Purpurin 18 with Improved Solubility: Potent Compounds for Photodynamic Therapy of Cancer - Pavlíčková, Vladimíra; Rimpelová, Silvie; Jurášek, Michal; Záruba, Kamil; Fähnrich, Jan; Křížová, Ivana; Bejček, Jiří; Rottnerová, Zdeňka; Spiwok, Vojtěch; Drašar, Pavel; Ruml, Tomáš (Molecules (Basel, Switzerland), 2019)
Purpurin 18 derivatives with a polyethylene glycol (PEG) linker were synthesized as novel photosensitizers (PSs) with the goal of using them in photodynamic therapy (PDT) for cancer. These compounds, derived from a second-generation PS, exhibit absorption at long wavelengths; considerable singlet oxygen generation and, in contrast to purpurin 18, have higher hydrophilicity due to decreased logP. Together, these properties make them potentially ideal PSs. To verify this, we screened the developed compounds for cell uptake, intracellular localization, antitumor activity and induced cell death type. All of the tested compounds were taken up into cancer cells of various origin and localized in organelles known to be important PDT targets, specifically, mitochondria and the endoplasmic reticulum. The incorporation of a zinc ion and PEGylation significantly enhanced the photosensitizing efficacy, decreasing IC50 (half maximal inhibitory compound concentration) in HeLa cells by up to 170 times compared with the parental purpurin 18. At effective PDT concentrations, the predominant type of induced cell death was apoptosis. Overall, our results show that the PEGylated derivatives presented have significant potential as novel PSs with substantially augmented phototoxicity for application in the PDT of cervical, prostate, pancreatic and breast cancer.
Keywords: photosensitizer; phototoxicity; nádorové buněčné linie; průtoková cytometrie; fluorescenční mikroskopie; singlet oxygen; porfyriny; Microscopy, Fluorescence; Porphyrins; live-cell fluorescence microscopy; Singlet Oxygen; fotochemoterapie; Cell Line, Tumor; cancer cells; cytotoxicity; Flow Cytometry; Humans; Photochemotherapy; photodynamic therapy; PEGylated purpurin 18; Solubility; singletový kyslík; rozpustnost; apoptosis; lidé; flow cytometry